Two decades of change in European general practice service profiles: conditions associated with the developments in 28 countries between 1993 and 2012. (2nd January 2016) - Schäfer, Willemijn L. A.; Boerma, Wienke G. W.; Spreeuwenberg, Peter; Schellevis, François G.; Groenewegen, Peter P.
Abstract: Objective: Evidence regarding the benefits of strong primary care has influenced health policy and practice. This study focuses on changes in the breadth of services provided by general practitioners (GPs) in Europe between 1993 and 2012 and offers possible explanations for these changes.Design: Data on the breadth of service profiles were used from two cross-sectional surveys in 28 countries: the 1993 European GP Task Profile study (6321 GPs) and the 2012 QUALICOPC study (6044 GPs). GPs' involvement in four areas of clinical activity (first contact care, treatment of diseases, medical procedures, and prevention) was established using ecometric analyses. The changes were measured by the relative increase in the breadth of service profiles. Associations between changes and national-level conditions were examined though regression analyses. Data on the national conditions were used from various other public databases including the World Databank and the PHAMEU (Primary Health care Activity Monitor) database.Setting: A total of 28 European countries.Subjects: GPs.Main outcome measure: Changes in the breadth of GP service profiles.Results: A general trend of increased involvement of European GPs in treatment of diseases and decreased involvement in preventive activities was observed. Conditions at the national level were associated with changes in the involvement of GPs in first contact care, treatment of diseases and, to a limited extent, prevention. Especially in countries with stronger growth of health care expenditures between 1993 and 2012 the service profiles have expanded. In countries where family values are more dominant the breadth in service profiles decreased. A stronger professional status of GPs was positively associated with the change in first contact care.Conclusions: GPs in former communist countries and Turkey have increased their involvement in the provision of services. Developments in Western Europe were less evident. The developments in the service profiles could only to a very limited extent be explained by national conditions. A main driver of reform seems to be the changes in health care expenditure, which may indicate a notion of urgency because there may be a pressure to curb the rising expenditures. Key points: Broad GP service profiles are an indicator of strong primary care in a country. It is expected that developments in the breadth of GP service profiles are influenced by various national conditions related to the urgency to reform, politics, and means. Between 1993 and 2012 the involvement of GPs in European countries in treatment of diseases increased and their involvement preventive activities decreased. The national conditions were found to be associated with changes in GPs' involvement as first contact of care, treatment of diseases, and, to a limited extent, prevention. More specifically, in countries with a stronger growth in health care expenditures, service profiles of European GPs have expanded more in the past decades.